The Influence of the Make A Match Learning Model on Student Learning Outcomes in Aqidah Akhlak Learning at MI Syamsul Iman NW in Senurus - Laela Patmawati (Indonesian Journal of Education and Social Humanities, 2025)
This study aims to determine the effect of the "Make a Match" learning model on student learning outcomes in the subject of Aqidah Akhlak with a focus on the material of Faith in the Prophet and Apostles. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were 20 students of MI Syamsul Iman NWDI Senurus. The data for this study were obtained using test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is quantitative Pre Experiment Design in the form of One Group Pretest and Posttest Design. The results of the study showed that there was an effect of the make a match learning model on student learning outcomes in the subject of Aqidah Akhlak with a focus on the material of Faith in the Prophet and Apostles. The results of the hypothesis test using the t test were 0.000 <0.05 and the average pretest value before being given treatment was 36.20. And the average posttest value after being given treatment was 70.20.